Financial literacy, morality, and organizational culture in preventing financial mismanagement: A study on village governments in Indonesia - I Made Sara; Ida Bagus Udayana Putra; Komang Adi Kurniawan Saputra; I Wayan Kartika Jaya Utama (Cogent Business & Management)
An empirical study was conducted with the aim of testing and analyzing the relationship between the variables of financial literacy, morality, organizational culture, and preventing financial mismanagement. The originality of this research lies in the integration of cultural factors in the organizational context and efforts to prevent financial mismanagement, which are rarely given the attention of researchers. Research design with survey techniques based on quantitative philosophy. The sample chosen to represent the population uses a proportionate random sampling technique. Data collection techniques using a structured questionnaire. Also, the collected data were analyzed using multiple linear regression models and moderation analysis. The results obtained from this study are based on the results of the analysis that financial literacy and morality have a significant effect on preventing financial mismanagement. Other empirical results find that organizational culture is able to moderate the relationship between financial literacy and morality towards preventing financial mismanagement. The contribution of this research is theoretically providing a theoretical phenomenon to the theory of reasoned action in terms of mismanagement behavior and the morale of government employees in the economic development sector of government. Practical contributions are given to village administration so that they consider the determinants of individual behavior in preventing financial mismanagement by increasing good organizational governance. The implication of this research is to provide a reference for village administration to reinforce rules to place more emphasis on individual and organizational behavioral factors.